Sequencing arrival flights with optimal time separation through en route speed control - Le, Hong Phuoc (2016)
The fast growth of air traffic demand in recent years has put a high pressure on the aviation organizations to increase the airport capacity. The conventional solutions such as building new airports or expanding current ones are not favorable since they require both huge capital investment and long term period to be implemented. Instead, it is more economical to improve the airport capacity through minimizing the aircraft delay time. This target can be achieved by optimizing the process of sequencing arrival flights in the airport’s TMA. The current sequencing method which is adopted by major airports in the world is First Come First Served (FCFS) policy. However, in spite of its simple usage and fair treatment to all airlines, FCFS does not necessarily results in optimal outcome in term of landing and delay time. This report aims to study the limitations of FCFS method, based on that suggests a more efficient sequencing policy, which is the sequencing method using Optimal Time Separation (OTS). The OTS sequencing method helps to reduce the aircraft delay by adjusting their arrival times in the airport’s TMA. This is performed through controlling the aircraft’s speed while they are still on en route journey. In order to verify the OTS sequencing method, three scenarios with different distributions of flight arrival times in Changi airport are constructed with the help of a fast time simulation software, AirTOp. After running the simulation, the results are analyzed and compared with the FCFS’s performance statistics in order to validate the improvement. Finally, recommendations of extended cases will also be suggested with the aim to enhance the OTS sequencing method’s reliability.